About the Journal - Thirakunkovit, Suthathip (FOYER: The Journal of Humanities, Social Sciences, and Education, 2022)
The Liberal Arts Journal, a publication of the Faculty of Liberal Arts, Mahidol University, was first published in 2018. Two semi-annual issues are scheduled for January - June and July-December each year. The Liberal Arts Journal publishes articles in Thai, English, and also other languages. The editor welcomes submissions of previously unpublished manuscripts in four categories: academic, research, review articles, and book reviews. Submitted manuscripts will be screened through double-blind review and read by at least two readers from relevant academic disciplines. Submitted manuscripts may not currently be reviewed for other journals. A complete version of articles appearing in conference proceedings may be considered, provided that the author(s) has extended the original by 60% at the least. In this case, an explicit acknowledgment of the first publishing is required in the extended manuscript. The Liberal Arts journal accepts articles in two clusters of academic areas. Liberal arts, humanities, social sciences, and education. Interdisciplinary/cross-disciplinary studies within the aforementioned disciplines.